"Too Bad to Be True". Swedish Economists on Keynes's 'The Economic Consequences of the Peace, 1919-1929' - Benny Carlson; Lars Jonung (Lund University, School of Economics and Management, Department of Economics, 2019)
This paper examines the response of five prominent Swedish economists, David Davidson, Gustav Cassel, Eli Heckscher, Knut Wicksell and Bertil Ohlin, to John Maynard Keynes's "The Economic Consequences of the Peace" and to the German reparations in the 1920s. When Keynes's book appeared, Davidson and Cassel strongly endorsed it. Heckscher also agreed with Keynes – "a bright spot in a time of darkness" – in a long review entitled "Too bad to be true". Inspired by his Malthusian view, Wicksell found the reparations impossible to meet unless German population growth was arrested. Germany should settle for a stationary population in exchange for reduced reparations. The contacts between the Swedes and Keynes became close after Keynes's book, in particular between Cassel and Keynes, competing for being the best-known economist in the world in the 1920s. The exchange of views took a new turn when Bertil Ohlin responded to an article by Keynes in The Economic Journal in 1929 on the transfer problem. In his comment, Ohlin summarized two previously overlooked articles from 1928 where he analyzed the transfer of the German reparations by using his theory of international trade. The famous Keynes-Ohlin discussion laid the foundation for the analysis of the transfer problem, bringing Ohlin international recognition. He emerged as the champion in this debate, which marked the end of academic interest in the German reparations in the interwar period. We also trace how Davidson, Cassel and Heckscher changed their appreciation of Keynes in the 1930s with the publication of the General Theory while Ohlin viewed the message of Keynes in the 1930s as consistent with the policy views of the Stockholm school of economics. We rely on newspaper and journal articles published by the Swedish economists, on half a dozen unpublished manuscripts by Wicksell as well as on the correspondence between Keynes and the Swedish economists.
Keywords: B13; B17; B27; E12; E44; F21; F35; F55; J11; N24; N44; 330; John Maynard Keynes; David Davidson; Gustav Cassel; Eli Heckscher; Knut Wicksell; Bertil Ohlin; Treaty of Versailles; reparations; the transfer problem; United Kingdom; Germany; Sweden; Malthusianism; World War I.